2012
DOI: 10.1186/1741-7015-10-91
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance N-acetyl cysteine treatment for bipolar disorder: A double-blind randomized placebo controlled trial

Abstract: BackgroundN-acetyl cysteine (NAC) is a glutathione precursor that has been shown to have antidepressant efficacy in a placebo-controlled trial. The current study aimed to investigate the maintenance effects of NAC following eight weeks of open-label treatment for bipolar disorder.MethodThe efficacy of a double blind randomized placebo controlled trial of 2 g/day NAC as adjunct maintenance treatment for bipolar disorder was examined. Participants (n = 149) had a Montgomery Asberg Depression Rating Score of ≥12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 35 publications
1
70
0
1
Order By: Relevance
“…23 Statistical analysis was conducted blind to treatment allocation. All analyses were conducted in accordance with the International Conference on Harmonization E9 statistical principles.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Statistical analysis was conducted blind to treatment allocation. All analyses were conducted in accordance with the International Conference on Harmonization E9 statistical principles.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…38 N-acetylcysteine has been shown to be potentially efficacious in a bewildering array of divergent disorders, from bipolar disorder 10,15,23 to schizophrenia, 6,14 obsessive-compulsive disorder, 39 nailbiting, 40 autism, 41 attention-deficit/hyperactivity disorder, 42 cocaine and cannabis abuse, 43 smoking, and blast traumatic brain injury, 44 although there are negative studies, including those in bulimia 45 and pediatric trichotillomania, 46 and the methodological quality of trials is highly variable. 4 As N-acetylcysteine has multiple mechanisms of action, it remains to be clarified if it works on common targets across disorders, such as oxidative stress or inflammation, or if some actions, such as glutamate-cysteine exchange, are more important to some disorders than others, such as addictions.…”
Section: Figure 2 Mean ± Se Estimates From Mixed-effects Model Repeamentioning
confidence: 99%
“…A 6-month double-blind RCT of add-on NAC to standard treatment showed a significant positive effect for depressive symptoms and functional outcome [87,88]. However, a study using NAC for the maintenance of bipolar disorder observed no result in recurrence or symptomatic outcomes [89]. …”
Section: The Future Of Research On Inflammation In Mddmentioning
confidence: 99%
“…The school newspaper information includes the school newspaper's header information, publishing units, organizers, competent authorities, authoritative email address, contact ways, etc. [6]. The…”
Section: Demand Analysis Of the School Newspaper Management Systemmentioning
confidence: 99%